Application of Meta Analysis Methods in Analyzing Temperature Effects on Laying Hens Production - Srinirat, Tanawut; Rakthai, Saksri (Journal of Vocational Education in Agriculture, 2024)
The purpose of this research was to apply of Meta Analysis Methods in analyzingtemperature effects on laying hens production .The research process was divided into 4 steps: 1) Gathering reliable data related to temperature effects on egg production from credible sources 2) Grouping temperature levels affecting egg production within the same rearing period to determine frequency and analyze trends3) Testing the differences in frequency of temperature levels affecting egg production using the Chi-Square Test and 4)Validating the temperature levels affecting egg production through in-depth interviews with experts in poultry research and faculty members responsible for undergraduate programs in Animal Production Technology.The results showed thatthe temperatures influencing egg production in starter chickens (0-6 weeks) are 32, 33, and 35 degrees Celsius, while temperatures impacting egg production in grower chickens (7-18 weeks) fall between 21-24 degrees Celsius. For layer chickens (19-80 weeks), the temperature range affecting egg production is between 18-30 degrees Celsius.